Burden of illness and quality of life in patients being treated for seasonal allergic rhinitis: a cohort survey. Issue 1 (9th October 2013) - Small, Mark; Piercy, James; Demoly, Pascal; Marsden, Helen
Abstract: Background: Allergic Rhinitis is an inflammatory disease which is characterised by burdensome nasal and/or ocular symptoms. This study aimed to assess the impact of symptoms (number of symptom‐free days (SFD) and Quality of Life (QoL)) in patients with Seasonal Allergic Rhinitis (SAR) being treated with fluticasone furoate (FF), mometasone furoate (MF) or fluticasone propionate (FP). Methods: In a cross‐sectional, non‐interventional, cohort analysis, primary care physicians and allergy specialists in France, Germany, and Spain were recruited via telephone interviews. Each physician prospectively recruited 4 SAR patients ‐ 2 receiving FF, 1 receiving MF and 1 receiving FP ‐ during June 2009. Patients answered questions on symptoms and completed questionnaires on QoL (mini‐rhinoconjunctivitis Quality of Life Questionnaire, RQLQ) and burden of illness (Pittsburgh Sleep Quality Index). Results: A total of 540 patients were recruited during June 2009. 88 patients were subsequently found to be ineligible and excluded from the analyses. In the 4 weeks prior to assessment, patients reported a mean of 14.58 (±8.42) SFD. Patients receiving FF had more SFD (mean 15.45 ±8.29) than patients receiving MF (adjusted mean difference ‐1.22, 95% Confidence Interval (CI) [‐3.16 to 0.72], p=0.434) or FP (adjusted mean difference ‐1.95, 95% CI [‐3.87 to ‐0.03], p=0.092), although statistical significance was not achieved. The mean RQLQ score was 1.54 (±1.06). Patients receiving FF had a better quality of life in the previous week (mini‐RQLQ score: mean 1.42, ±1.04) than patients receiving MF (adjusted mean difference 0.28, 95% CI [0.03 to 0.52], p=0.052) or FP (adjusted mean difference 0.18, 95% CI [‐0.05 to 0.41], p=0.244). Again, none of these results achieved statistical significance. Conclusions: At the height of the allergy season, patients with SAR suffer symptoms approximately 50% of the time, and report an impact on their QoL. No significant differences were observed between FF, FP and MF related to SFD or QoL. Trial registration: ClinicalTrials.gov identifier: NCT01199757